2000
DOI: 10.1007/s101620010043
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mutation of the Gene for Cellular Glutathione Peroxidase (Gpx1) Increases Noise-Induced Hearing Loss in Mice

Abstract: ABSTRACTcochlea injury, and cochlear degeneration. Such impairment produces characteristics expected of some mutations associated with age-related hearing loss and Reactive oxygen species (ROS) and oxidative stress have been implicated in cochlear injury following loud offers one possible mechanism for their action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
147
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(155 citation statements)
references
References 32 publications
(3 reference statements)
5
147
0
3
Order By: Relevance
“…Impaired function of antioxidant enzymes caused by genetic variation has been postulated as leading to failure of cellular responses against the toxic effects of ROS and subsequent peroxidative cell injury. Studies of knock-out models of Gpx1 and Sod1 have shown that deletion in the two antioxidant genes can lead to both age-related and noise-induced HL [51][52][53]. These mice show the phenotypic characteristics of ARHL.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Impaired function of antioxidant enzymes caused by genetic variation has been postulated as leading to failure of cellular responses against the toxic effects of ROS and subsequent peroxidative cell injury. Studies of knock-out models of Gpx1 and Sod1 have shown that deletion in the two antioxidant genes can lead to both age-related and noise-induced HL [51][52][53]. These mice show the phenotypic characteristics of ARHL.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Keywords cochlea; free radical; noise; hearing; antioxidant; vasodilation Mechanical destruction of cells in the organ of Corti was once assumed to be the primary cause of noise-induced hearing loss (NIHL) [1][2][3][4][5][6][7][8], with perhaps some effect of reduced blood flow to the inner ear [9][10][11][12][13][14][15][16][17][18]. We now know that another key factor is intense metabolic activity that results in production of excess free radicals [19][20][21][22][23] and lipid peroxidation products [24]. Noise-induced production of reactive oxygen species (ROS) in the cochlea has now been well characterized, and several recent reviews are available [25][26][27].…”
mentioning
confidence: 99%
“…Upregulation of the endogenous antioxidant glutathione reduces NIHL and cell pathology [44,45], whereas the opposite is observed with reduced endogenous antioxidants [20,22,23,44]. That exogenous antioxidant agents reduce sensory cell death and NIHL has been well demonstrated in animal studies using a variety of free radical scavengers [24,[44][45][46][47][48][49][50][51][52][53][54][55][56], including several studies with dietary antioxidants [50,[57][58][59][60].…”
mentioning
confidence: 99%
“…Repeated blast exposure in mice showed significant increase in the expression of antioxidant enzymes, superoxide dismutase 3, and glutathione peroxidase 4 in the hippocampus and midbrain, suggesting a protective mechanism in central auditory processing (Tables 1 and 4). The influence of glutathione peroxidase and superoxide dismutase in noiseinduced hearing loss has also been reported [12,31,[33][34]. Reactive oxygen species showed an increase in the brain following repeated blast exposures [36].…”
Section: Discussionmentioning
confidence: 81%
“…Another large class of molecules involved in auditory signaling is centered on the calcium regulating proteins, which are known to have broad functions in age-and noise-related hearing loss or protection [18,[22][23][24][25][26]. The significance of reactive oxygen species and heat shock proteins in age-and noise-related auditory impairments are also reviewed in detail [10,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%